Hubungan antara Kecukupan Energi dan Status Gizi dengan Produktivitas Kerja (PT. Timur Megah Steel Gresik Tahun 2019) - Himaya Himaya; R. Bambang Wirjatmadi (Amerta Nutrition, 2019)
Background: Laborers have a central role in achieving company goals that cannot be separated from their work productivity factors. Several factors that can improve work productivity in terms of nutrition are energy sufficiency and nutritional status. The difference of energy adequacy and nutritional status of each labor caused differences in works productivity.Objectives: This study aims to analyze the relation between energy adequacy and nutritional status with the productivity of labors in the packing section (setting nuts and bolts) in PT. Timur Megah Steel Gresik. Methods: This study was an observational study with a case-control research design. The sample size used in this study was 38 workers. The sample consisted of case samples and case-control. There are 19 workers with low productivity in the case sample and 19 workers with high productivity in the control sample. Data were analyzed using Spearman correlation.Results: The results of the analysis test showed that there was a relationship between energy adequacy (p<0,001) and nutritional status based on anthropometry (p<0,001) with work productivity, but there was no correlation between nutritional status based on biochemical/hemoglobin level status (p=0.172) with work productivity.Conclusions: There was a significant correlation between energy adequacy and nutritional status by anthropometry with work productivity.ABSTRAKLatar Belakang: Tenaga kerja mempunyai peranan sentral dalam mencapai tujuan perusahaan yang tidak dapat terlepas dari faktor produktivitas kerjanya. Kecukupan energi dan status gizi tenaga kerja yang masing-masing berbeda mengakibatkan adanya perbedaan produktivitas kerja yang dimiliki.Tujuan: Menganalisis hubungan antara kecukupan energi dan status gizi dengan produktivitas pada tenaga kerja laki-laki bagian packing (setting mur dan baut) PT. Timur Megah Steel Gresik.Metode: Penelitian ini merupakan penelitian observasional dengan design penelitian case control. Besar sampel yang digunakan dalam penelitian ini adalah 38 tenaga kerja. Sampel terdiri dari sampel kasus yaitu 19 tenaga kerja dengan produktivitas kurang/rendah dan sampel kontrol yaitu 19 tenaga kerja dengan produktivitas baik/tinggi. Analisis data menggunakan uji korelasi spearman.Hasil: Terdapat hubungan kecukupan energi (p=0,000) dan status gizi berdasarkan antropometri (p=0,000) dengan produktivitas kerja, namun tidak terdapat hubungan status gizi berdasarkan biokimia/status kadar hemoglobin (p=0,172) dengan produktivitas kerja.Kesimpulan: Kecukupan energi dan status gizi (antropometri) yang meningkat dapat meningkatkan produktivitas kerja.